(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Osteoarthritis of the knee is a common chronic musculoskeletal disease causing prolonged pain, limited mobility, and reduced quality of life, especially in the elderly. In conservative treatment, multimodal approaches are increasingly used to optimise symptom control and improve function. This study was conducted to evaluate the added value of shockwave therapy, in combination with a basic Traditional Chinese Medicine (TCM) protocol, for patients with primary knee osteoarthritis. Subjects and Methods: This was a controlled, pre- and post-hoc clinical intervention study of 60 inpatients with primary knee osteoarthritis. Patients were conveniently selected and divided into two equal groups. The study group received shockwave therapy combined with the "Tam Ty Thang" herbal formula, electroacupuncture, and massage; the control group received a TCM protocol without shockwave therapy. The primary endpoints included pain level on the VAS, motor function on the WOMAC, and knee flexion range of motion. The follow-up period was 15 days. Results: Before treatment, the two groups were similar in age, gender, duration of illness, BMI, initial pain level, WOMAC score, knee flexion range of motion, and radiographic injury severity (p > 0.05). After 15 days of treatment, the mean VAS score in the study group decreased to 2.73 ± 0.69, lower than that in the control group (3.23 ± 0.57; p < 0.05). The overall WOMAC score in the study group decreased to 19.72 ± 2.56, lower than that of the control group (21.83 ± 3.43; p < 0.05). The increased knee flexion range of motion after 15 days in the study group reached 17.53 ± 3.51 degrees, higher than in the control group at 13.97 ± 4.39 degrees (p < 0.05). Adverse effects were observed at a low rate, mainly transient mild pain increase or mild bruising at the treatment site; no serious events or treatment discontinuations were recorded. Conclusion: In the 15-day short-term follow-up period, the addition of shockwave therapy to the basic Traditional Chinese Medicine regimen was associated with greater improvements in pain and selected functional indicators in patients with primary knee osteoarthritis. Further large-scale studies with a more rigorous design and longer follow-up periods are needed to confirm the method’s sustained efficacy.